IMPROVING VOCABULARY USING TGT (TEAMS GAMES TOURNAMENT) METHOD - Rihanah, Hilyah; Sudiyono, Sudiyono (PROJECT (Professional Journal of English Education), 2020)
This study aims to improve vocabulary through Team Game Tournament Techniques in class IX students of one of the junior high schools conceived. The sample of this research was 32 students. The method used in this research was action research applied in two cycles. Then the data was collected by using multiple choice tests (pre-test and post-test). The results that the TGT method can be improved vocabulary students, it was showed from the table score that increased from the mean score of pre-test, post-test cycle 1 and post-test cycle 2. The mean score of pre-test was 55.94 , the mean score of the pre-test cycle was 74.37 and the mean score of the post-test cycle 2 80.31.it is assumed that the TGT method is effective to improve vocabulary students and then the use of the TGT technique makes students more motivated. Keywords:  Vocabulary, TGT (Teams Games Tournament), CAR